The Efficacy and Safety of Qiming Granule for Dry Eye Disease: A Systematic Review and Meta-Analysis - Yang, Maoyi; Hu, Zhipeng; Yue, Rensong; Yang, Liangjun; Zhang, Boxun; Chen, Yuan (Frontiers in Pharmacology, 2020)
Background: Dry eye disease (DED) is a common complication in clinical practice. Qiming granule, a traditional Chinese patent medicine, is widely used in treating DED in China. However, its effect is still largely unknown. Objectives: This research aims to evaluate the efficacy and safety of QG on DED. Methods: Three English database and four Chinese databases without restriction on language and publication bias were searched. Qualified literature was selecting according to inclusion and exclusion criteria, extracted the data and conducted a meta-analysis. Results: A total of 11 articles were included in this meta-analysis. The methodological quality of included studies was low. The results showed that QG was effective for DED (RR:1.26, 95%CI:1.12 to 1.41, P=0.0001). The results combined with random effects model showed that QG could significantly prolong the tear film break up time (MD: 2.93, 95% CI: 2.22 to 3.65, P＜0.00001), increase the amount of tears in patients with DED (MD: 2.94, 95% CI: 1.83 to 4.04, P<0.00001) and repair the corneal defects in patients (MD: -0.71, 95% CI: -1.25 to -0.17, P＜0.00001). Conclusions: This study found that despite of the apparently positive results of some outcomes, it is premature to confirm the efficacy of QG in treating DED. More high-quality studies are still needed in the future to further confirm the efficacy and safety.